Automatic geometry alteration when designing for additive manufacturing - Martinsson, Julian (My University, 2019)
Abstract The space industry has developed an interest in converting some of its production from traditional manufacturing to metal additive manufacturing. This may prove beneficial to the space industry due to their generally low production volumes, and their need to minimize product mass. The transition from traditional to additive manufacturing can be difficult, and requires designers to take heed of a new set of design and manufacturing constraints. To aid the designers this thesis project has aimed to create a software which automatically alters the geometry of 3D STLmodels. The purpose of the alterations is to reduce the model’s need for support structures. Reducing the support structures is necessary to reduce material waste, and to decrease the time required to process the model after it has finished printing. A prototype software was created which can handle simple geometries, but struggles when the model complexity increases. Two main problems were encountered: difficulty to handle overhang surfaces that point directly down, and unintended software behavior which caused issues mostly prevalent in high complexity models. These issues could not be resolved during the course of this project, but could likely be overcome in the future. Finally, this thesis project resulted in the creation of a software prototype capable of altering the geometry of low complexity models.
Keywords: Produktion; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Production; Innovation & Entrepreneurship; Mechanical Engineering